Literature Review: Teknik Cognitive restructuring pada CBT dalam Meningkatkan Self-esteem - Latifah; Eliana Dewi, Imalatul Khairat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effectiveness of the cognitive restructuring technique within the Cognitive Behavioral Therapy (CBT) approach in enhancing students’ self-esteem. The method used is a literature review by analyzing four relevant articles. The results indicate that cognitive restructuring consistently improves self- esteem by transforming negative thinking patterns into more rational and adaptive ones. This technique proves effective in various contexts, including general students, victims of body shaming, and approaches that integrate spiritual values. These findings suggest that cognitive restructuring is a flexible and applicable intervention for school counseling services. Further research is recommended to explore qualitative approaches and the integration of technology in counseling practices.